Prenatal antibiotic exposure in pregnancy and early childhood socioemotional development. Issue 2 (29th March 2022) - Fish‐Williamson, Adi; Hahn‐Holbrook, Jennifer; Hobbs, Mark; Wallander, Jan; Morton, Susan M. B.
Abstract: Background: Antibiotic exposure in pregnancy is associated with reduced microbiome diversity in the infant gut. Given that recent research has shown that early microbiome health can impact child socioemotional development, we examined the relationship between prenatal antibiotic exposure in pregnancy and childhood socioemotional developmental outcomes using a large, nationally representative longitudinal dataset. Methods: A sample of 4800 diverse families were assessed from the population cohort of the Growing Up in New Zealand Study (GUiNZ), which prospectively follows children starting in the last trimester of pregnancy into early childhood. Socioemotional development was measured using a composite score derived from seven commonly used socioemotional tasks administered between 9 months and 4.5 years of child age, addressing emotional expression understanding, regulation of emotions and behavior, and social problem solving and relationship skills. A national comprehensive pharmaceutical database was used to determine children's prenatal antibiotic exposure. Multivariate linear regressions models were used to examine the effects of the timing (trimester) and dosage (number of courses) of prenatal antibiotic exposure on socioemotional development, with and without statistically adjusting for confounding factors addressing maternal health, socioeconomic status, maternal age, and child sex. Results: In unadjusted analyses, antibiotic exposure was inversely associated with child socioemotional development. However, after statistically adjusting for important confounds, socioemotional development was not associated with prenatal antibiotic exposure at any dosage or trimester of pregnancy (all β  ≤ −0.02). Conclusion: Prenatal antibiotic exposure does not appear to impact early childhood socioemotional development. Maternal health and sociodemographic factors are confounded with antibiotic exposure and socioemotional development, a fact that should be considered in future research examining the effects of prenatal antibiotic exposure on child health. These findings may be reassuring to families who are concerned about the long‐term effects of antibiotics in pregnancy on child health outcomes.